2011
DOI: 10.1111/j.1365-2958.2011.07885.x
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the CtrA regulon in development of stress resistance in obligatory intracellular pathogen Ehrlichia chaffeensis

Abstract: Summary Ehrlichia chaffeensis is an obligate intracellular bacterium that causes human monocytic ehrlichiosis. Ehrlichiae have a biphasic developmental cycle consisting of dense-cored cells (DCs) and reticulate cells (RCs). Isolated DCs are more stress resistant and infectious than RCs. Here, we report that a response regulator, CtrA was upregulated in human monocytes at the late growth stage when DCs develop. E. chaffeensis CtrA bound to the promoters of late-stage transcribed genes: ctrA, ompA (peptidoglycan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
109
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(119 citation statements)
references
References 80 publications
(144 reference statements)
4
109
0
Order By: Relevance
“…The Helix-turn-helix (HTH) Motif of BolAs Is Potentially Involved in DNA Binding-Currently, only bacterial BolA_H members have been shown to act as transcriptional regulators by binding to gene promoters (34,35), whereas Uvi31ϩ, a BolA_H from Chlamydomonas reinhardtii, likely exhibits endonuclease activity (36). The capacity to bind nucleic acids is in line with the fact that BolA possesses an overall fold related to the one found in type II K-homology (KH) domain-containing proteins (33) known to bind nucleic acids.…”
Section: Atbola Structures Support the Existence Of Two Differentmentioning
confidence: 99%
“…The Helix-turn-helix (HTH) Motif of BolAs Is Potentially Involved in DNA Binding-Currently, only bacterial BolA_H members have been shown to act as transcriptional regulators by binding to gene promoters (34,35), whereas Uvi31ϩ, a BolA_H from Chlamydomonas reinhardtii, likely exhibits endonuclease activity (36). The capacity to bind nucleic acids is in line with the fact that BolA possesses an overall fold related to the one found in type II K-homology (KH) domain-containing proteins (33) known to bind nucleic acids.…”
Section: Atbola Structures Support the Existence Of Two Differentmentioning
confidence: 99%
“…Given its demonstrated role in AmOmpA and ApOmpA function, K58 might contribute to the adhesin capabilities of all Anaplasma and Ehrlichia species OmpA proteins. Our findings presented here, together with a previous report that E. chaffeensis OmpA contributes to infection of monocytic cells (19), prompt us to propose that ehrlichial OmpA proteins also are adhesins that contribute to cellular invasion and do so by recognizing sialylated and fucosylated glycans in a manner that involves the conserved lysine.…”
Section: Discussionmentioning
confidence: 78%
“…Given the demonstrated roles of A. phagocytophilum and E. chaffeensis OmpA proteins in promoting infection of mammalian host cells (17,19,21), we sought to determine if AmOmpA performs a similar adhesin function for A. marginale. An alignment of ApOmpA and AmOmpA revealed that the two exhibit 52.33% sequence identity (17).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations